Design of Axial Flux Type Permanent Magnet Coupling with Halbach Magnet Array for Optimal Performance Considering Eddy Current Loss Reduction Using 3-D Finite Element Method - Hyeon Jang, Gang; Won Seo, Sung; Woo Kim, Chang; Hun Shin, Kyung; Nah, Junghyo; Young Choi, Jang (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study proposes and verifies a design method that considers the permanent magnet (PM) loss reduction of axial flux permanent magnet coupling (PMC), to replace mechanical coupling.Methods/Statistical analysis: In this study, the design of an axial magnetic flux PMC is performed using a threeâ€“dimensional (3D) commercial finite element (FEM) analysis program, and an optimum design is performed through parametric analysis. In addition, we designed a PMC that minimizes loss by analyzing the PM eddy current loss when using divided magnets.Findings: We found that some parameters (thickness of the PM, number of poles, ratio of inner radius to outer radius) act on the magnetic torque of the axial flux coupling. Using these results, we could obtain the design point. Further, to reduce the PM eddy current loss in the designed coupling, we used the PMs divided radially and circumferentially to obtain the magnet shape to minimize the loss. In addition, the fabricated coupling proved that the design results of the 3D FEM matched with the experimental results.Improvements/Applications: We propose an optimal design method of an axial flux PMC using 3D FEM, and a method to reduce eddy current loss using divided magnetsÂ